Successful Nonoperative Treatment of Isolated Popliteus Tendon Avulsion Fractures in Two Adolescents - Scott D. McKay; Andrew Holt; Thomas Stout; Viola Qafalijaj Hysa (Case Reports in Orthopedics, 2014)
Isolated popliteal tendon avulsion fractures are relatively uncommon in the pediatric population as other posterolateral lateral structures are often involved. This report describes two skeletally immature male patients who presented with knee injuries without ligamentous instability and were subsequently diagnosed with isolated popliteus tendon avulsion fractures. Both of these patients were managed nonoperatively and had subjectively full recoveries. As the treatment for isolated popliteal tendon avulsion fractures is still unclear, the report here may contribute to strategies regarding conservative treatment of these injuries.